The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3201/eid2607.190846
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Chikungunya Virus in an Urban Slum, Brazil

Abstract: I n the 21st century, chikungunya virus (CHIKV) has emerged as a mosquitoborne disease of global relevance, causing large epidemics because of its widespread dissemination in tropical and subtropical areas (1). Infected persons usually develop an acute febrile illness associated with joint pains, myalgia, headache, and other signs and symptoms that can

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
33
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 41 publications
6
33
1
1
Order By: Relevance
“…For example, Hagan et al[ 6 ], in a four-year cohort study in Salvador reported proximity to accumulated trash and rat sightings as risk factors for leptospirosis (see also Fig D in S1 File ). Chikungunya infection in Salvador is also higher in households without paved access [ 32 ]. Here, though, neither of these factors was related to exposure and sero-prevalence in the SEM, but were themselves driven by sanitation and physical environment near the household.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Hagan et al[ 6 ], in a four-year cohort study in Salvador reported proximity to accumulated trash and rat sightings as risk factors for leptospirosis (see also Fig D in S1 File ). Chikungunya infection in Salvador is also higher in households without paved access [ 32 ]. Here, though, neither of these factors was related to exposure and sero-prevalence in the SEM, but were themselves driven by sanitation and physical environment near the household.…”
Section: Discussionmentioning
confidence: 99%
“…Chikungunya virus has re-emerged in many parts of the world and is considered to be a continuous global threat [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. The reason for this resurgence is not fully elucidated, but is believed to be multifactorial, such as increased vector susceptibility and perhaps climate change [ 6 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chikungunya virus has re-emerged in many parts of the world and is considered to be a continuous global threat (32,(46)(47)(48)(49)(50)(51)(52)(53). The reason for this resurgence is not fully elucidated, but is believed to be multifactorial, such as increased vector susceptibility and perhaps climate change (6,54,55).…”
Section: Discussionmentioning
confidence: 99%